Identifying the Jewish Eupolemoi: an onomastic approach - Sørensen, Søren Lund (The journal of Jewish studies, 2015)
The article investigate the into the Eupolemos, Hellenistic Jewish historian and ambassador, who was sent on an embassy to the Romans by Judas Maccabee, among the Jews in antiquity in order to discover whether an identification of the two namesakes is plausible. It looks at several geographical and chronological evidences that argues it is in fact very likely that Eupolemos the ambassador and Eupolemos the historian were one and the same person.